Foreign body in the mandible: a case report - Dadá, Abdul Habib Mahomed; Fernandes, Gilberto Coelho; Inácio, Nelsa Maria José Sisto; Vasconcelos, Niucha; Dadá, Mahomed Sidique Abdul Cadar (Brazilian Journal of Case Reports, 2023)
Foreign bodies are defined as any object that is foreign to a specific anatomical location. They are very common in clinical practice and every doctor ends up dealing with these cases, especially in emergency consultations. The aim of this case report is to draw dentists' attention to accidents with foreign bodies in the oral cavity that can occur in dental offices. The authors describe a case report of a 41-year-old female patient, with a dental bur lodged in her jaw, despite being asymptomatic. An expectant approach was adopted. It is important to check the entire mouth and pharynx in cases where a tooth or dental instrument is missing.